Effect of Dissolved Organic Carbon in Modifying the Toxicity of Inorganic Mercury to Fish and Its Implication on Mercury Accumulation by Fish in Ponds And Lakes - Subhendu Datta; Shyamal Chandra Sukla Das (Journal of Indian Fisheries Association, 2017)
Due to global industrialization, large quantity of metals enters to the aquatic ecosystems. The behaviour of metals in the aquatic systems is dependent on various environmental factors. The present study, was conducted to know the effect of dissolved organic matter on the level of toxicity of inorganic mercury (Hg) on the common carp, Cyprinus carpio var. communis fry (av. length: 3.9 0.5 cm and av. weight: 0.9 0.20g). Acute toxicity test was conducted employing static bioassay method with constant aeration. At different dissolved organic carbon (DOC) levels, e.g., 0.02, 3.3, 7.6, 10.7, 14.5, 23.8, 32.4 and 44.5 mg/L, the ET50 values (h) of mercury at 1.0 mg/L were 30.74, 102.85, 116.82, 150.37, 157.34, 185.46, 234.09 and 297.89h, respectively. As the concentration of DOC increased (0.02 to 44.5 mg/L), with the increasing amount of natural organic matter; the toxicity of mercury decreased almost 10 times (ET50 value increased from 50 30.7 to 297.9 h). This substantial reduction of acute toxicity of mercury was due to the formation of mercury complexes with dissolved organic carbon that contains organic ligands, which have S , N and O containing functional groups for complexation. This provides the protective capacity of many natural lakes and wetlands of tropical countries which have high concentration of DOM against metal toxicants like mercury. To test this hypothesis, mercury level in the sediment, water and fish flesh (common carp and catla) of three sewage-fed fisheries units of Kolkata were tested. Though at the entry point the sediment contained mercury (0.36 – 0.65 ppm), mercury level was either below detectable limit or below the permissible limit (<0.001-0.058 ppm) in water and fish flesh of fish culture area.